Pathological Findings in COVID-19 as a Tool to Define SARS-CoV-2 Pathogenesis. A Systematic Review - Mondello, Cristina; Roccuzzo, Salvatore; Malfa, Orazio; Sapienza, Daniela; Gualniera, Patrizia; Ventura Spagnolo, Elvira; Di Nunno, Nunzio; Salerno, Monica; Pomara, Cristoforo; Asmundo, Alessio (Frontiers in Pharmacology, 2021)
Introduction: The World Health Organization declared the COVID-19 pandemic in March 2020. Covid-19 still represents a worldwide health emergency, which causes a severe disease that has led to the death of several patients. The pathophysiological mechanism of SARS-CoV-2 determining the tissue damage is not clear and autopsy can be a useful tool to improve the knowledge of this infection and, thus, it can help achieve a timely diagnosis and develop an appropriate therapy. This is an overview of the main post-mortem findings reporting data on the infection effects on several organs. Methods: A systematic literature search was conducted in the PubMed database searching for articles from 1 January to 31 August 2020. The articles were selected identifying words/concepts in the titles and/or abstracts that indicated the analysis of the morphological/pathological tissue injuries related to SARS-CoV-2 disease by several investigations. Results: A total of 63 articles were selected. The main investigated tissue was the lung showing a diffuse alveolar damage (DAD) frequently associated with pulmonary thrombotic microangiopathy. Inflammatory findings and vascular damage were observed in other organs such as heart, liver, kidney, brain, spleen, skin and adrenal gland. The immunohistochemical analysis showed tissue inflammatory cells infiltrates. The virus presence was detected by several investigations such as RT-PCR, immunohistochemistry and electron microscope, showing the effect of SARS-CoV-2 not exclusively in the lung. Discussion: The evidence emerging from this review highlighted the importance of autopsy to provide a fundamental base in the process of understanding the consequences of SARS-CoV-2 infection. COVID-19 is strictly related to a hyper inflammatory state that seems to start with DAD and immuno-thrombotic microangiopathy. Massive activation of the immune system and microvascular damage might also be responsible for indirect damage to other organs, even if the direct effect of the virus on these tissues cannot be excluded.